Hamming Code at Marker-Based Augmented Reality on the Android Platform for Teaching Philosophy of Batik - Wiwid Widyanto; Rosa Ariani Sukamto; Alejandro Rosales Pérez; Isma Widiaty (Journal of Computers for Society, 2020)
Batik is one of the many cultural heritage of Indonesia that has high artistic value and has become the hallmark of a nation that must be preserved. Augmented reality (AR) is a technology that adds virtual objects into the real world. This technology could provide new ways of delivering information to users, a more interactive way. In this research, a system of marker-based AR tracking used the introduce batik was made. One type of augmented reality is AR marker-based tracking. To track markers, several there are steps that must be performed on every frame received from the camera android smartphone. Phase tracking in this study includes of conversion of images from the camera frame into a grayscale image, detects the contour, perspective transformations, and decoding algorithm using Hamming Code. Test-based results by author, tracking markers on this system could properly track 100% of each marker in normal circumstances, within a certain range depending on the size of the marker and at an angle of 45°. Test-based results by author, tracking markers on this system could properly track 100% of each marker in normal circumstances, within a certain range depending on the size of the marker and at an angle of 45°.